Nilai-Nilai Moderasi Beragama dalam Al-Qur’an dan Hadis: Kajian Ulum al-Qur’an, Ulum al-Hadis, dan Pembentukan Karakter - Masturah, Yasmin Hafidzoh (Lembaga Publikasi Ilmiah Nusantara, 2025)
This article discusses the concept of religious moderation in the Qur’an and Hadith through the study approach of Ulum al-Qur'an and Ulum al-Hadith, along with its implications for character formation. Religious moderation is an essential value in fostering a balanced attitude in practicing religion, whether in aspects of worship, social life, or culture. This research employs thematic interpretation (tafsir maudhu‘i) to analyze Qur’anic verses and prophetic traditions related to the principles of moderation. In this study, religious moderation is understood as a teaching that avoids extreme attitudes both in belief and in action while emphasizing the importance of tolerance, justice, and balance. Through Ulum al-Qur’an and Ulum al-Hadith, this paper identifies texts that affirm the importance of moderation in religious practice and the development of personal character in accordance with Islamic teachings. The findings indicate that the concept of religious moderation serves not only as a guideline for worship but also for social interaction among human beings. Thus, character formation based on the values of religious moderation can contribute to creating a harmonious and just society.